Economic Recovery Efforts: Boosting East Java’s Export Performance Through Mapping The Competitiveness of Commodities - M. Fahmi Priyatna; Sonia Anggun Andini (East Java Economic Journal, 2021)
As an effort to encourage the export performance of East Java, concrete and comprehensive information and mapping are needed regarding the level of competitiveness of export commodities and their future prospects. This is necessary so that policy makers can devise the right strategy in each category of commodity competitiveness. To map the competitiveness of commodities and their prospects in the future, this study uses a combined technique of Revealed Comparative Advantage (RCA) and Constant Market Share Analysis (CMSA). RCA demonstrates static competitiveness at one time period (2020), while CMSA represents dynamic competitiveness in two time periods (2016 and 2020). With the merger of these two methods, East Java export commodities are divided into four categories, namely great amounting to 426 commodities, sunset amounting to 426 commodities, sunrise amounting to 649 commodities, and poor amounting to 919 commodities. The optimization of the four categories can be divided into two major parts of international cooperation, there are through the expansion of trade exports for the great and sunrise categories, as well as efforts to attract foreign direct investment (FDI) for the sunset and poor categories.